Aplikasi Informasi Pemasaran Berbasis Web Pada CV. Yuri Pontianak - Fara Dina; Yolantika Nur; Ardiyansyah Ardiyansyah (Jurnal Sistem Informasi Akuntansi, 2020)
CV. Yuri is a convection company that accept orders like a toga, almamater, t-shirt, elementary school uniform, junior high school uniform and daily service uniform. In marketing activities, the company user door to door system and goes directly to the consumers place to introduction their product. Certainly, this is takes a lot of time and high cost. This company also still uses manual system that is used paper media to do important data rcording lie a order data, product data, raw material data, and employee data. Cause of manual system, the data often damage like a torn, wet, and loss of the data. Therefore, the writer tired to make final project regarding the application of marketing information for CV. Yuri Pontianak. This application is a solution for companies in developing service to consumers while improving the manual recording system to be computerized system. By using this application, companies can reach a wider range ot consumer and can record important data to be more effective and efficient